Shakespeare's cinema of love : a study in genre and influence - White, R. S. (Manchester University Press, 2016)
Shakespeare's cinema of love addresses the question, how much has Shakespeare influenced modern film genres? Convincing arguments are made for the links between his comedies of love and genres such as 'screwball' comedy, musicals, romantic comedy and tragic love films.
Introduction: Shakespeare shaping modern movie genres 1.'Madly mated': The Taming of the Shrew and odd-couple comedy 2. Dreams in the forest: romantic comedy 3. 'The guy's only doing it for some doll': musical comedy 4. Of errors and eros: a brief digression on twins 5. Comedy of disguise and mistaken identity 6. 'Star-crossed lovers': Romeo and Juliet and romantic tragedy Conclusion Index.
Keywords: Shakespeare, William, -- 1564-1616 -- Influence.; Shakespeare, William, -- 1564-1616 -- Film adaptations.; Shakespeare, William, -- 1564-1616; Motion pictures -- Plots, themes, etc.; Film genres.; Love in motion pictures.; Cinéma -- Intrigues, thèmes, etc.; Genres cinématographiques.; Amour au cinéma.; Film Theory & Criticism.; PERFORMING ARTS -- Film & Video -- History & Criticism.; DRAMA -- Shakespeare.; LITERARY CRITICISM -- Shakespeare.; DRAMA -- English, Irish, Scottish, Welsh.; PERFORMING ARTS / Film & Video / History & Criticism; Film genres; Influence (Literary, artistic, etc.); Love in motion pictures; Film adaptations